Reproductive Biology of the Mola Carplet Amblypharyngodon mola (Hamilton) (Cypriniformes: Cyprinidae) from Netrakona Water - Saha, Bimal Kanta; Islam, M Rafiqul; Saha, Aparna; Hossain, M Altaf (Bangladesh Journal of Scientific and Industrial Research, 2010)
Some aspects of the reproductive biology viz. sex ratio, fecundity and reproductive periodicity of Amblypharyngodon mola were studied during March 2004 through February 2005 in Netrakona. Sex ratio was found to be 1:2.03. Fecundity varied from 1,291 to 12,797 with a mean value 5,751.46 ± 3,321.73 eggs. The relationships between Fecundity (F) and Total Length (TL), Standard Length (SL), Total Weight (TW), Gonadal length (GL) and Gonadal Weight (GW) were calculated and found to be highly significant. The mean of ova diameter was 1.4 ± 0.35mm. Different methods used to study the reproductive periodicity showed that the periodicity of A. mola starts from March and continues up to August with a peak in May. Key words: Reproductive biology, Reproductive periodicity, Amblypharyngodon mola. DOI: 10.3329/bjsir.v44i3.4414 Bangladesh J. Sci. Ind. Res. 44(3), 377-379, 2009